Foreign Otherness in Japanese Media Exploring the Japanese SelfThrough Images of Latin America. - Forero-Montoya, Betsy Stella (Universidad De Los Andes, 2021)
Betsy Forero-Montoya is an Associate Professor in the School of Arts and Humanities at Universidad de los Andes (Colombia). She received a PhD in Japa-nese Studies from Tsukuba University and a Master's of Arts from Sophia University. She has been teach-ing and conducting research on Japan for almost two decades. She has authored articles and book chap-ters on media portrayal of gender and ethnicity, and on popular culture.